The use of handcuffs in police activity (Research, Society and Development, 2022)
The use of handcuffs that are made by public security agents after the approach, and whose main objective is to immobilize and not cause escape, or bodily injury to the agent, or the immobilized person or third parties. It is sought to be carried out cautiously, but it is not possible to know if the individual arrested may cause one of these situations because the agent does not know what the individual may commit in a situation like this. The essential fundamental rights of the person must be fulfilled, without subjecting to shame or embarrassment by the use of handcuffs, also the handcuff cannot cause any injury to the individual. Due to the lack of legal discipline on the subject, this study reports a brief history of the use of handcuffs and discusses the subject of what is provided in the binding precedent n° 11 of the Federal Supreme Court, which considered the use of handcuffs in exceptional cases lawful, such as in adolescents and pregnant women.